Layering of communication networks and a forward-backward duality - Cyran, Michael; Schotsch, Birgit; Huber, Johannes; Fischer, Robert F.H. (SCC 2017 - 11th International ITG Conference on Systems, Communications and Coding, 2019)
In layered communication networks there are only connections between intermediate nodes in adjacent layers. We propose a layering procedure to transform an arbitrary network into an equivalent layered one. Applying network coding to (equivalent) layered topologies enlightens the structure of networks more clearly and provides advantages in the theoretical treatment of communication networks, as well as when numerically simulating such networks. Furthermore, for the bidirectional communication between a source/destination pair, we derive a forward-backward duality for linear network codes, which can be seen as an analogon to the uplink-downlink duality in MIMO communication systems.
CRIS-Team Scopus Importer:2019-10-22